Understanding nascent plasmons and metallic bonding in atomically precise gold nanoclusters. Issue 7 (28th January 2022) - Du, Xiangsha; Liu, Zhongyu; Higaki, Tatsuya; Zhou, Meng; Jin, Rongchao
Abstract : Cryogenic spectroscopy measurements on atomically precise gold nanoclusters with nascent plasmon resonance reveal a non-thermal origin of electron-gas formation. The birth of plasmon resonance from concerted excitonic transitions is discussed. Abstract : The metallic bond is arguably the most intriguing one among the three types of chemical bonds, and the resultant plasmon excitation ( e.g. in gold nanoparticles) has garnered wide interest. Recent progress in nanochemistry has led to success in obtaining atomically precise nanoclusters (NCs) of hundreds of atoms per core. In this work, thiolate-protected Au279 (SR)84 and Au333 (SR)79 NCs, both in the nascent metallic state are investigated by cryogenic optical spectroscopy down to 2.5 K. At room temperature, both NCs exhibit distinct plasmon resonances, albeit the NCs possess a gap (estimated 0.02–0.03 eV, comparable to thermal energy). Interestingly, we observe no effect on plasmons with the transition from the metallic state at r.t. to the insulating state at cryogenic temperatures (down to 2.5 K), indicating a nonthermal origin for electron-gas formation. The electronic screening-induced birth of metallic state/bonding is discussed. The obtained insights offer deeper understanding of the nascent metallic state and covalent-to-metallic bonding evolution, as well as plasmon birth from concerted excitonic transitions.